Effects of Lunar Near‐Surface Geology on Moonquakes Ground Motion Amplification. Issue 9 (11th September 2022) - Amrouche, Mohamed; Weber, Renee C.; Schmerr, Nicholas; Iqbal, Wajiha
Abstract: Lunar seismology has focused on exploring the Moon's seismic activity and its internal structure. However, less attention has been given to site specific, near‐surface geology‐related amplification of seismic waves on the Moon. Here, we quantified ground‐motion amplifications of seismic waves due to local site conditions at the Apollo landing sites. We analyzed Apollo Passive Seismic Experiments seismometer recordings of 30 artificial and natural impacts and estimated the mid‐period (0.1–3 Hz) ground‐motion amplification at each site. We applied techniques commonly used in engineering seismology to understand the local site effects, such as the Horizontal over Vertical Spectral Ratio (HVSR) and the Reference Site Method (RSM) on lunar seismic data. The HVSR and the RSM show convergent spectral ratios specific for each landing site. To correlate these empirical results estimated from lunar artificial and meteoroid impact events with the local site geology, we simulated ground motion amplification using 2D finite difference modeling of lunar geological models and estimated the best geological setting capable of producing a similar frequency response to those observed at each Apollo landing site. Correlation results from the empirical methods and the simulated models show similarities ranging between 79% and 92%, a correlation more than 90% between the RSM and the HVSR results, and similarity exceeding 96% between RSM estimations using different reference sites. These results demonstrate the prominence of a local site geology dependent amplification for frequencies between 0.1 and 3 Hz. Plain Language Summary: Near‐surface geology can play a significant role in seismic wave propagation and amplification during earthquakes, which is what scientists call the seismic site effects. While these site effects are becoming more and more understood here on Earth, their effects remain poorly studied in the context of seismic wave propagation on the Moon. In order to understand how the near‐surface geology affects seismic wave amplification on the Moon, we applied two different methods commonly used for earthquake site effects studies to moonquake data recorded at the different Apollo landing sites. Results from these different methods were convergent and highlight specific responses at each landing site. To be sure that our results are the effects of the near‐surface geology on the Moon, we recreated numerical simulation models that mimic the amplification behavior obtained from meteoroid data. We successfully generated numerical models with specific site geology that reproduce amplifications similar to the ones observed at each landing site, demonstrating that local site geology can amplify the ground motions on the Moon. Key Points: We quantified ground motion amplification due to local geology on the lunar surface using different methods used in engineering seismology We validated our empirical results using numerical simulations and modeled the best geological models that replicate similar amplification We achieved a good correlation between the simulated and the empirical results, proving the occurrence of site amplifications on the Moon